2007
DOI: 10.4049/jimmunol.178.12.7694
|View full text |Cite
|
Sign up to set email alerts
|

OX40-Mediated Differentiation to Effector Function Requires IL-2 Receptor Signaling but Not CD28, CD40, IL-12Rβ2, or T-bet

Abstract: Ag-specific CD4 T cells transferred into unirradiated Ag-bearing recipients proliferate, but survival and accumulation of proliferating cells is not extensive and the donor cells do not acquire effector functions. We previously showed that a single costimulatory signal delivered by an agonist Ab to OX40 (CD134) promotes accumulation of proliferating cells and promotes differentiation to effector CD4 T cells capable of secreting IFN-γ. In this study, we determined whether OX40 costimulation requires supporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…In contrast, IFN-␥ production was not affected by the absence of IL-2 signaling, which is consistent with the ability of CD8 T cells to develop the capacity to produce IFN-␥ in an IL-2-independent manner (42). Interestingly, recent work from Williams et al (43) has demonstrated that anti-OX40 treatment can drive CD4 T cells into Th1 effector cells via an IL-2-dependent mechanism. In contrast to the results obtained with CD8 T cells, the OX40-mediated increase in CD4 T cell-specific IFN-␥ production was dependent upon IL-2 signaling.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast, IFN-␥ production was not affected by the absence of IL-2 signaling, which is consistent with the ability of CD8 T cells to develop the capacity to produce IFN-␥ in an IL-2-independent manner (42). Interestingly, recent work from Williams et al (43) has demonstrated that anti-OX40 treatment can drive CD4 T cells into Th1 effector cells via an IL-2-dependent mechanism. In contrast to the results obtained with CD8 T cells, the OX40-mediated increase in CD4 T cell-specific IFN-␥ production was dependent upon IL-2 signaling.…”
Section: Discussionsupporting
confidence: 74%
“…Although this data seems to be at odds with the premise that IL-12 drives a Th1 response, previous studies have shown that IL-12 (p35)-deficient mice infected with lymphocytic choriomeningitis virus produce equivalent levels of IFN-␥ when compared with wild-type mice (31). Furthermore, a recent study demonstrated IL-12R␤2 did not play a significant role in the differentiation of Ag-specific CD4 T cells following OX40 engagement (32). Therefore, in anti-OX40-stimulated CD4 T cells, IL-12 appears to be more important for survival than Th1 differentiation.…”
Section: Il-12 Signaling Is Critical For Ox40-enhanced Cd4 T Cell Surmentioning
confidence: 85%
“…Although TCR stimulation is necessary to up-regulate OX40, additional signals are required for inducing optimal OX40 expression. For example, CD28 signaling can contribute to OX40-mediated co-stimulation [8], [9], although CD28 itself is not required for the generation of OX40-dependent responses [10], [11]. Since CD28 ligation leads to increased IL-2Ralpha (CD25) expression and IL-2 production [12], it is unclear whether CD28-B7 signaling contributes to OX40-mediated co-stimulation directly or through an IL-2-dependent mechanism.…”
Section: Introductionmentioning
confidence: 99%